Does Competition Matter in The Malaysian Banking System? - Nur Afizah Muhamad Arifin; Roslina Mohamad Shafi; Imani Mokhtar (Information Management and Business Review, 2023)
The transition from financial repression to financial liberalization, which led to cross-border capital flows and the expansion of the financial sector, has had a significant impact on the global financial market. Competition could pass through or interact with the impact of financial liberalization on financial stability. A liberalized banking sector prompted commercial banks to intensify risk-taking activities, which ultimately could affect financial stability.  This paper examines the effect of financial liberalization on financial stability and the roles of competition as the interacting variable using a panel data analysis based on a sample of 43 banks in Malaysia.  Results from the Malaysian banking sector indicate that increased competition will affect the stability of the financial system. Lastly, competition needs to be set at the best possible level so that financial stability can be well preserved.